DINAMIKA KEPEMIMPINAN NYAI DI PESANTREN BUDAYA JAWA - ‘Aeni, Fitri Nur (Martabat: Jurnal Perempuan dan Anak, 2017)
The position and role of women can not be separated from the prevailing socioculturalsystem. Women in various civilizations often receive unjust treatmentin the social system, women may only access spaces located in the domesticsector. The same is true of Javanese women. Javanese women are attachedto the label âKonco ing wingkingâ, someone who is given the responsibilityof taking care of the back of the household and should not appear in front.This research specifically examines the role of pesantren in Javanese culture.This research is interesting because the role nyai often sink and lose whencompared with the Kyai.Keywords : Nyai, Pesantren, The Role of Women